Комплексная математическая модель процессов в турбине с регулируемыми отборами пара - Бойко, Анатолий Владимирович; Усатый, Александр Павлович (НТУ "ХПИ", 2016)
В работе приведена общая система уравнений, описывающая термогазодинамические процессы во всех составных частях турбины с регулируемыми отборами пара, а также приводится метод ее решения. Решение данной системы уравнений позволяет проводить комплексный тепловой расчет турбины, состоящей из системы парораспределения (соплового или дроссельного) с одно или двух венечной регулирующей ступенью, а также остальной проточной части, сформированной из ступеней давления. При этом, коэффициенты скорости для сопловых решеток регулируемых поворотных диафрагм, обеспечивающих регулирование отборов пара на производственные и теплофикационные нужды, определяются в результате решения общей системы уравнений.

This article is dedicated to improving and expanding the ability of mathematical model of processes in the steam turbines flow path with the aim of implementation of integrated thermal steam turbines computation with controlled steam extractions. The mathematical model is based on a complex system of equations. Solving these equations, you can perform the calculation of the turbine, which consists of steam distribution system, control stage and the rest of the turbine with plenty of pressure stages. This is achieved by increasing the dimension of the common system of equations. In the number of unknown parameters of the overall system of equations the velocity coefficients of all nozzle grids, that have rotary diaphragm, are added. This system of equations is solving numerically using the Fletcher-Reeves conjugate gradient method.
Integrated mathematical model of the processes in the turbine with adjustable steam extraction
Keywords: теплофикационная паровая турбина; регулируемая поворотная диафрагма; коэффициент скорости; тепловой расчет; cogeneration steam turbine; rotary diaphragm; velocity coefficient